(untitled) (Italian Review of Legal History, 2020)
Since many years, traditional civil justice is in crisis. To overcome the serious difficulties and to lighten the process, in compliance with fundamental guarantees, the Italian legal system has tried to value the use of alternative tools for resolving family infighting and interpersonal conflicts. Some of the most recent systems are the civil and commercial mediation and assisted negotiation and many other practices that, with many differences, aim to resolve disputes outside the ordinary procedural way. Finally, between doctrine and best practice, there have also been attempts to exclude a priori, or at least to limit, the emergence of contrasts by using the so-called ‘pre-conflictual’ pacts. The tendency to reduce the conflict was already characteristic in the procedural code of 1865, that in fact provided for an attempt at mandatory conciliation as a condition for the prosecution of the case, according to Napoleonic model and which was still maintained, with some adjustments, in pre-unification legislation. Between the end of the nineteenth century and the first half of the twentieth century, in different fields, have also been introduced colleges aimed at resolving some specific types of controversy disputes, in respect of which the various arbitration panels or arbitrators - called upon to act in an equitable manner - appeared more suitable and ductile than the ordinary place of proceedings; moreover, in these cases, dictated as a whole by the urgent needs of war and the extraordinary nature of certain hypotheses, the doctrine has in a substantially uniform way identified real special jurisdictions. The current procedural code, which has been reformed several times, dates back to 1940: it enhances judicial conciliation at various stages of the process, facilitating the early termination of the judgment, at a time prior to the delivery of a decision. Even civil law offers tools for extra-judicial conciliation, such as the transaction, particularly convenient when looking for a timely result or in any case it is too uncertain the outcome of the judgment. Arbitration is certainly one of the most important alternative means of resolving conflict. Its history is much older than the movement animated a few decades ago in the Anglo-Saxon world under the acronym ADR. It is an articulated procedure entirely replacing the ordinary judgment. Over time, the relationship with state jurisdiction has changed differently, especially with regard to the nature and effectiveness of the concluding act of the procedure. Even in the most ancient times there are examples of alternative forms of composition of the lite, different from the instruments offered by the dominant political system. We can certainly think of the “episcopalis audientia” or of those forms of negotiating composition, even in the criminal sphere, proper to a society in which justice is not yet conceived as a typical expression of an apparatus of power that, has not yet developed organically. The tendency towards pacification is a natural requirement. Even in the most remote times, the involvement of a third party to rely on to overcome a conflict seemed a natural solution, especially when public structures were not yet defined by the almost monolithic exercise of justice or when in any case they did not guarantee solutions in line with the expectations of the subsidiaries. Just as the private paci or certain forms of pecuniary composition in criminal matters can demonstrate, in the pre-modern state realities, the tension to the pacification of a conflict in almost private form, negotiated privately, although not as a guarantee for those involved. The arbitration, although known by Roman law, takes on new characters in the municipal age, during which the notarial practice elaborates formulas more suited to the needs of the time and the doctrine has interpreted the Romanistic discipline in a completely new way. Arbitration, in some matters, was often made mandatory for conflict resolution. In modern times, the institute was not able to maintain the same liveliness. The absolutist ambitions of the principles have tended to lead to a strengthening of central justice, reducing the spaces traditionally left to private justice. The evolution of the legislation, especially of the French ordonnances, clearly shows a stiffening of the arbitration, which gradually assumes an increasingly procedural structure, losing the elements of negotiation of the most ancient tradition. Even the Savoy legislation tends to have a significant impact, albeit with minimal interventions, on the importance of the institution. The exasperated criticism of technical justice advocated by the French Revolution led, at first, to greatly enhance the definition of arbitration, but with some extreme provisions which imposed that, it eliminates the most typical aspect of the institution. Only the Napoleonic code succeeded in achieving a new balance between private justice and state justice. The institution was once again an expression of private will, although meticulously regulated by state law. The codes of the Restoration in procedural matters tended to maintain the Napoleonic approach, leading that model towards the unitary code of 1865, which placed arbitration in the opening. It was considered not as a way of ending disputes, but as a way of avoiding them. The arbitration awards were the subject of significant litigation, both in the appeal and in the nullity proceedings, on which more research is still being carried out.